2008
DOI: 10.4022/jafib.v1i1.394
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Prediction of Symptomatic Atrial Fibrillation In Patients with Rheumatic Mitral Stenosis and Normal Sinus Rhythm

Abstract: In rheumatic mitral stenosis (RMS), mitral valve area is reduced, creating an obstruction to the blood flow between the left atrium (LA) and the left ventricle (LV), causing an elevation in LA pressure. Elevation in LA pressure has several important effects including enlargement of the LA, atrial arrhythmias, and an increase in pulmonary venous pressure. RMS increases the risk of both atrial fibrillation (AF) and thromboembolism, causing an important health care problem in developing countries. The prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…[26] The presence of severe pulmonary hypertension and a left atrial size >50 mm were identi ed as echocardiographic ndings that suggested a trend toward a higher prevalence of paroxysmal atrial brillation in this study, which was consistent with the ndings of Serdar Bicergolu in 2008. [27] However, in our study, the association was not statistically signi cant. (CI 95% P= 0.466).…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…[26] The presence of severe pulmonary hypertension and a left atrial size >50 mm were identi ed as echocardiographic ndings that suggested a trend toward a higher prevalence of paroxysmal atrial brillation in this study, which was consistent with the ndings of Serdar Bicergolu in 2008. [27] However, in our study, the association was not statistically signi cant. (CI 95% P= 0.466).…”
Section: Discussioncontrasting
confidence: 72%
“…In reality, there are differences between the two study designs; our cross-sectional study and the Serdars were prospective studies, which might provide them with an opportunity to track earlier who developed AF. [27] Since all patients in our study had preserved LV systolic function, it was impossible to determine whether reduced left ventricular systolic function was associated with a greater risk of paroxysmal atrial brillation in the presence of severe MS, as was the case in other studies, such as that of Moreyra et al [23] As shown in Table 6, aortic stenosis tended to be associated with the emergence of paroxysmal atrial brillation, even though this association did not reach statistical signi cance. This could be due to reduced LV compliance associated with AS leading to further atrial cardiomyopathy, which in turn acts as grounds for the development of PAF.…”
Section: Discussionmentioning
confidence: 65%